The role and importance of virtual currencies in asset recovery (Academic Journal of Internal Affairs, 2021)
Within asset recovery the current topics deal with the area of detection and seizure of virtual means of payment (e.g., crypto currencies). It is an area where only a few professionals experienced in the field of asset recovery deal with, as it requires knowledge radically different from traditional investigative methods. Statistics show that the proliferation of virtual currencies is growing, especially among organized crime groups. Therefore, it is essential to have special knowledge of this area by as many staff members of the relevant authorities as possible, in order to achieve successful law enforcement actions in this field.
Keywords: asset recovery; coercive measure; cryptocurrency; bitcoin